Macroeconomic Foundations for Comparative Political Economy - Satvir Singh (Al-Qanṭara, 2022)
The global financial crisis and ensuing weak growth have increased interest in macroeconomic issues within comparative political economy (CPE). CPE, particularly the dominant Varieties of Capitalism approach, has based its analyses on mainstream economics, which limits analysis of the relation between distribution and growth and neglects the role finance plays in modern economies. It overstates the stability of the capitalist growth process and understates the potential effectiveness of government interventions. Baccaro and Pontusson have suggested a post-Keynesian (PK) theory of distribution and growth as an alternative. This article generalizes their point. PK theory highlights the instability of the growth process and lends itself to an analysis of income distribution and power relations. The article identifies the analysis of financialization and financial cycles, the understanding of neoliberal growth models, and the political economy of central banks as areas where PK economics provides specific insights for CPE. It also highlights that these arguments have important implications for government policy in an era of secular stagnation with ongoing social, distributional, and economic crises.